Boiler bottom ash appreciation through alkalinizer production: a circular economy proposal (Research, Society and Development, 2022)
The new concepts of Circular Economy (EC) and changes in the world energy matrix drive the consumption of biomass as an alternative source for energy production. In this context, eucalyptus (Eucalyptus) chips are a promising source of biomass. The burning of this biomass produces ash residue, which needs to be disposed of properly or recovered to reduce the environmental and economic impacts of this residue. This review article aims to discuss the valorization of industrial boiler biomass ash with a focus on the production of alkalizing agent. The recovery of this residue has taken place in different ways, with the use of alkalizing properties for soil correction as the most common within industrial practices of waste management. On the other hand, the solubilization of the oxides present in the ash and the use of this extract as an alkalizing agent in the treatment of water and effluents can be an alternative to conventional alkalizing agents. This would increase the possibilities of valuing the ash, reducing the negative impacts of energy generation processes. Studies and conditions for the production of alkalizing agent are not clear in the literature.